Evaluation of wheat straw gasification in fluidized bed gasifier using aspen plus - ÖZVEREN, UĞUR (My University, 2019)
Biomass gasification is an encouraging thermochemical process that converts this residue mainly into syngas, which may be applied to electricity, generate heat, and fuels. However, the biomass gasification is quite complex and dependent on many interrelated and independent variables because of gasification reactions including water-shift and Boudouard reactions. In this study, a novel biomass gasification model for wheat-straw was developed to simulate the air–steam gasification in a fluidized bed for syngas production using Gibbs reactor (RGIBBS) in Aspen Plus simulator, which is based on the minimization of Gibbs energy, has been used in this work for the whole gasification unit. To reveal the effects of gasification parameters; gasifier temperature, steam flow rate were investigated using sensitivity analysis. The major evaluation criteria are estimation accuracy and generality of the developed gasifier model. The model is validated by data from literature and found relatively to be in good agreement. Results show that higher steam over air composition increases heating value of syngas.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG)